Sipakatau Ecopack: Leveraging Rice Straw for Sustainable and Eco-Friendly SME Packaging Solution - Faiqa, Nurul; Baharuddin, Aris; Wafirah, Nabila Salma; Jusman, Muhridho Jaya (PINISI Discretion Review, 2024)
Indonesia, as an agrarian country, holds significant potential in utilizing agricultural by-products such as rice straw. Sipakatau EcoPack, a Small and Medium-sized Enterprise (SME) in South Sulawesi, applies rice straw as a material to produce environmentally friendly food packaging. By processing rice straw sourced from farmers in South Sulawesi, and utilizing additional materials such as wheat flour, NaOH 10% powder, water, and PVA, Sipakatau EcoPack successfully creates biofoam as an alternative to styrofoam. The production process involves three stages: pulping, dough making, and molding using a specialized pressing machine. This article discusses market potential, production processes, as well as marketing strategies and business legality of Sipakatau EcoPack, including Intellectual Property Rights (IPR) protection. Sipakatau EcoPack demonstrates that environmentally friendly products not only provide ecological benefits but also offer significant economic opportunities.